Cytoalbuminologic dissociation in Asian patients with Guillain‐Barré and Miller Fisher syndromes. Issue 1 (March 2015) - Wong, Anna Hiu Yi; Umapathi, Thirugnanam; Nishimoto, Yukihiro; Wang, Yu Zhong; Chan, Yee Cheun; Yuki, Nobuhiro
Abstract Cerebrospinal fluid (CSF) protein level, cell count, and its relationship to the timing of lumbar puncture were collected from patients with Guillain‐Barré syndrome (GBS) and Miller Fisher syndrome (MFS) from various Asian centers. A total of 507 patients with GBS were studied. Overall, 56% had elevated CSF protein level. This was significantly lower than that reported in a recent Dutch study (56% vs 64%). Cytoalbuminologic dissociation was also lower in the Asian cohort (55% vs 64%), with a significantly higher proportion of patients with mild pleocytosis (26% vs 15%). A lower proportion of the 164 patients with MFS had elevated CSF protein level (38% vs 56%), mild pleocytosis (11% vs 26%), and cytoalbuminologic dissociation (41% vs 55%) compared to patients with GBS. In both conditions, cytoalbuminologic dissociation was linked to the timing of lumbar puncture. Cytoalbuminologic dissociation was only observed in half of the Asian patients with GBS and MFS, and it is strongly dependent on the timing of the lumbar puncture.